Disentangling the relationship between gender and work–family conflict: An integration of theoretical perspectives using meta-analytic methods. - Shockley, Kristen M.; Shen, Winny; DeNunzio, Michael M.; Arvan, Maryana L.; Knudsen, Eric A. (Journal of Applied Psychology, 2017)
Implicit in many discussions of work-family issues is the idea that managing the work-family interface is more challenging for women than men. We address whether this intuition is supported by the empirical data via a meta-analysis of gender differences in work-family conflict (WFC) based on more than 350 independent samples (N > 250,000 workers). Challenging lay perceptions, our results demonstrate that men and women generally do not differ on their reports of WFC, though there were some modest moderating effects of dual-earner status, parental status, type of WFC (i.e., time-, strain-, vs. behavior-based), and when limiting samples to men and women who held the same job. To better understand the relationship between gender and WFC, we engaged in theory-testing of mediating mechanisms based on commonly invoked theoretical perspectives. We found evidence in support of the rational view, no support for the sensitization and male segmentation perspectives, and partial support for the asymmetrical domain permeability model. Finally, we build theory by seeking to identify omitted mediators that explain the relationship between gender and work-interference-with-family, given evidence that existing theoretically specified mechanisms are insufficient to explain this relationship. Overall, we find more evidence for similarity rather than difference in the degree of WFC experienced by men and women. (PsycINFO Database Record